The need of enterprise content management system (ECMS) in organization / Noor Shakila Ahmad - Ahmad, Noor Shakila (2014)
The aim of this study is to find out the need of Enterprise Content Management System (ECMS) in organization. This research study also aims to find out the problems facing by organizations and potential benefits of ECMS to organizations after deploy ECMS. In this study, thirteen (13) respondents were participating. They were from case study organizations Sure Reach Records Management (SRRM) and Bank Muamalat Malaysia Berhad (BMMB) in four (4) different departments. The respondents have experience and knowledge in ECMS. They also currently involve in ECM Project in manage their contents. The methods used in this study are interview and questionnaire. From the analysis, the result show that the problems and potential benefits are the force factor or trigger to organizations needs ECMS. Organizations needs system to manage the contents and get the fully benefits from it. These research findings contribute to helps organization understand their needs and helps company to better understand benefits implement ECMS.